Restoring the Platelet miR-223 by Calpain Inhibition Alleviates the Neointimal Hyperplasia in Diabetes - Su, Meiling; Fan, Shunyang; Ling, Zhenwei; Fan, Xuejiao; Xia, Luoxing; Liu, Yingying; Li, Shaoying; Zhang, Yuan; Zeng, Zhi; Tang, Wai Ho (Frontiers in Physiology, 2020)
Platelet hyperactivity is the hallmark of diabetes, and platelet activation plays a crucial role in diabetic vascular complications. Recent studies have shown that upon activation, platelet-derived miRNAs are incorporated into vascular smooth muscle cells (VSMCs), regulating the phenotypic switch of VSMC. Under diabetes, miRNA deficiency in platelets fails to regulate the VSMC phenotypic switch. Therefore, manipulation of platelet-derived miRNAs expression may provide therapeutic option for diabetic vascular complications. We seek to investigate the effect of calpeptin (calpain inhibitor) on the expression of miRNAs in diabetic platelets, and elucidate the downstream signalling pathway involved in protecting from neointimal formation in diabetic mice with femoral wire injury model. Using human cell and platelet coculture, we demonstrate that diabetic platelet deficient of miR-223 fails to suppress VSMC proliferation, while overexpression of miR-223 in diabetic platelets suppressed the proliferation of VSMC to protect intimal hyperplasia. Mechanistically, miR-223 directly targets the insulin-like growth factor-1 receptor (IGF-1R), which inhibits the phosphorylation of GSK3β and activates the phosphorylation of AMPK, resulting in reduced VSMC dedifferentiation and proliferation. Using a murine model of vascular injury, we show that calpeptin restores the platelet expression of miR-223 in diabetes, and the horizontal transfer of platelet miR-223 into VSMCs inhibits VSMC proliferation in the injured artery by targeting the expression of IGF-1R. Our data present that the platelet-derived miR-223 suppressed VSMC proliferation via the regulation miR-223/IGF-1R/AMPK signaling pathways, and inhibition of calpain alleviates neointimal formation by restoring the expression of miR-223 in diabetic platelet.